2011
DOI: 10.1007/s00405-011-1492-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of glial growth factor and nerve growth factor on the recovery of traumatic facial paralysis

Abstract: The aim of this study was to assess the effects of Glial growth factor (GGF) and nerve growth factor (NGF) on nerve regeneration in facial nerve anastomosis. In this study, approximately a 1-mm segment was resected from the facial nerve and the free ends were anastomosed. All animals underwent the same surgical procedure and 30 rabbits were grouped randomly in three groups. Control group, the group without any medications; NGF group, the group receiving 250 ng/0.1 ml NGF in the epineurium at the site of anasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…It is indicated that exogenous treatment of NRG β1 would increase the length of regenerating axons and improve the functional outcome after sciatic nerve injury [32], [33]. Pharmacological report also documented that following facial nerve transection, NRG β1 could increase the Sc nuclei and reduce the myelin debris [34]. Our current study was thus in good agreements with these findings in which application of NRG β1 also showed an increase of migrated Sc and speeding the nerve regeneration following end-to-side neurorraphy (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that exogenous treatment of NRG β1 would increase the length of regenerating axons and improve the functional outcome after sciatic nerve injury [32], [33]. Pharmacological report also documented that following facial nerve transection, NRG β1 could increase the Sc nuclei and reduce the myelin debris [34]. Our current study was thus in good agreements with these findings in which application of NRG β1 also showed an increase of migrated Sc and speeding the nerve regeneration following end-to-side neurorraphy (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The use of recombinant or virally expressed NRG1 therapeutically following peripheral nerve injury has shown some efficacy in promoting axon regeneration (Chen et al , 1998; Joung et al , 2010; Fricker and Bennett, 2011; Yildiz et al. , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Rats treated every 24 h for 4 days beginning 24 h after sciatic nerve injury with recombinant NRG1 type II showed improvement in measures of axon regeneration, including axon diameter and myelin thickness, assessed at 2 months postinjury, and had accelerated functional recovery as determined by the sciatic functional index (SFI) [92]. In addition, in rabbits with a facial nerve transection, treatment with NRG1 type II at the time of injury and 24 and 28 h postinjury resulted in an increase in SC nuclei and a reduction in myelin debris at 2 months postinjury [93]. Furthermore, rats injected intraneurally into both the proximal and distal stump of the sciatic nerve at the time of transection with an adenovirus expressing just the β-EGF domain of NRG1 type I increased the length of regenerating axons, expression of GAP43 at 3 weeks following injury and showed an improved functional outcome determined by gait ana lysis [94].…”
mentioning
confidence: 97%